2014
DOI: 10.1063/1.4872307
|View full text |Cite
|
Sign up to set email alerts
|

Non-perturbative modelling of energetic particle effects on resistive wall mode: Anisotropy and finite orbit width

Abstract: A non-perturbative magnetohydrodynamic-kinetic hybrid formulation is developed and implemented into the MARS-K code [Liu et al., Phys. Plasmas 15, 112503 (2008)] that takes into account the anisotropy and asymmetry [Graves et al., Nature Commun. 3, 624 (2012)] of the equilibrium distribution of energetic particles (EPs) in particle pitch angle space, as well as first order finite orbit width (FOW) corrections for both passing and trapped EPs. Anisotropic models, which affect both the adiabatic and non-adiabati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
113
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(115 citation statements)
references
References 47 publications
2
113
0
Order By: Relevance
“…The most severe one is probably the inconsistency of the evaluation of the perturbed drift kinetic energy perturbation from the trapped fast ions, with the assumption of the cylindrical geometry. Nevertheless, we believe that this does not affect the qualitative physics of the drift kinetic damping, as confirmed by full toroidal computations [7,14,15]. Moreover, the resistive layer contribution, as we shall show, is rigorously evaluated in our example.…”
mentioning
confidence: 51%
“…The most severe one is probably the inconsistency of the evaluation of the perturbed drift kinetic energy perturbation from the trapped fast ions, with the assumption of the cylindrical geometry. Nevertheless, we believe that this does not affect the qualitative physics of the drift kinetic damping, as confirmed by full toroidal computations [7,14,15]. Moreover, the resistive layer contribution, as we shall show, is rigorously evaluated in our example.…”
mentioning
confidence: 51%
“…On the other hand, with an assumption that all the equilibrium pressure comes from TPs (termed "full therm al" case), the kinetic response shows behavior similar to that of the thermal case. N ear the no-wall limit, the response am plitude in the full thermal case is slightly larger than that o f the other two cases, due to the lack of one extra adiabatic term arising from the boundary integration in the particle phase space for the slowing down EPs with finite birth energy [28]. This extra term eventually plays a dam ping role.…”
mentioning
confidence: 89%
“…In experiments, cotangential NBI was em ployed, with two injection tangency radii o f 76 and 115 cm, producing EPs with anisotropic distributions in the particle pitch angle space. This motivates us to test the sensitivity o f kinetic response against the EP models, m a r s -k implements an anisotropic NBI model that is suitable for ITER [28]. We choose an averaged injection tangency radii o f 95.5 cm and an ITER-like beam width param eter (<5f = 0.123).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[11,12], In order to check whether the RWM excitation mecha nism described above plays a role in experiments, it is necessary to take into account other damping mechanisms, which are not included in our model. For instance, it has been reported that resonant interactions with energetic particles can stabilize RWMs [9,28], and the effect of such interactions on the excitation mechanism described in this Letter should be clarified. As discussed in [9], the resonant interaction of RWMs with energetic particles depends on the relationship between the rotation frequency and the characteristic frequencies of energetic particles, and this interaction becomes ineffective in some cases.…”
mentioning
confidence: 93%